(untitled) (Journal of Environmental Science and Natural Resources, 2013)
The Barind tract of Bangladesh suffers from frequent drought due to erratic rainfall distribution. In the present study details analysis of rainfall data has been carried out for the years 1971-2010. The Standardized Precipitation Index (SPI) which is followed by gamma distribution is used to evaluate drought vulnerability based on frequency and severity of drought events at multiple time steps (3, 5 and 12 months). Drought severity maps are generated in a GIS (Geographical Information System) environment using inverse distance weighting method. Critical (threshold) rainfall values are derived for each station at multiple-time steps in varying drought categories to determine least amount of rainfall required to avoid from drought initiation. The study found that drought vulnerability portrays a very diverse but consistent picture with varying time steps. Analysis and interpretation of the map shows a similar spatial distribution of drought in pre-monsoon season but in monsoon season rainfall deficits shifts its position time to time and occurred in certain discrete pockets. In 12 months period the spatial distribution of drought was almost similar with monsoon season. In pre-monsoon season drought severity was higher in north eastern part of the study area compare to other parts. The study also evident that critical threshold values of rainfall to avoid drought condition was higher in the northern part of high Barind than southern part. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14832 J. Environ. Sci. & Natural Resources, 5(2): 287-293 2012